Redo aortic root replacement reutilizing 22-year patent modified Cabrol grafts. (15th December 2016) - Tanaka, Akiko; Afaq, Shaikh; Atay, Scott; Estrera, Anthony
Abstract: Long-term patency of modified Cabrol technique in composite aortic root replacement is not well documented. We report a unique case in which a patient presented for prosthetic valve dysfunction with patent Cabrol grafts 22 years after composite root replacement requiring redo aortic root. This case also demonstrates how modified Cabrol grafts can be reutilized in aortic root replacement without compromising adequate fluid dynamics.